Biology of Polyomavirus miRNA - Zou, Wei; Imperiale, Michael J. (Frontiers in Microbiology, 2021)
Polyomaviruses are a family of non-enveloped DNA viruses with wide host ranges. Human polyomaviruses typically cause asymptomatic infection and establish persistence but can be reactivated under certain conditions and cause severe diseases. Most well studied polyomaviruses encode a viral miRNA that regulates viral replication and pathogenesis by targeting both viral early genes and host genes. In this review, we summarize the current knowledge of polyomavirus miRNAs involved in virus infection. We review in detail the regulation of polyomavirus miRNA expression, as well as the role polyomavirus miRNAs play in viral pathogenesis by controlling both host and viral gene expression. An overview of the potential application of polyomavirus miRNA as a marker for the progression of polyomaviruses associated diseases and polyomaviruses reactivation is also included.